Pengaruh Disiplin Kerja dan Pengembangan Karir Terhadap Kinerja Karyawan Pada PT Bank Tabungan Negara Kantor Cabang Jakarta Melawai - Palupi, Titi Kurnia; Purwatiningsih, Purwatiningsih; Ratih Setyo Rini (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
Company performance is very dependent on the employees themselves. Therefore, personnel requires a lot of attention from management, one of wich is the discipline of each employee, work performance, and career development potential. The research method used is descriptive quantitative. With a sample size of 70 people. Data collection techniques using observation, interviews, questionnaires and documentation. The results of the research show that there is a partially significant influence between work discipline on employee performance, this is proven based on the results of partial tests or examinations with a total probability value of 0.000 < 0.05 and a calculated t value. > t table namely r 5.287 > 1.99601. There is a partially significant influence between career development and employee performance, this is proven based on the results of partial tests or examinations with a probability value of 0.000 < 0.05 and a calculated value > t table, namely 4.213 > 1.99601. There is a significant and simultaneous influence between work discipline and career development on employee performance at PT Bank Tabungan Negara Jakarta Melawai Branch Office, this is proven based on the results of F tests or simultaneous tests with a total probability value of 0.000 < 0.05 and a calculated F value. > F table is 71.627 > 3.13.